Mixossarcoma esplênico em cão - Zambarda, Taís Teixeira; de Souza, Mariana de Jesus; Cannavon, Jéssica Moreira; Felten, Clarisse; Pavarini, Saulo Petinatti; Pöppl, Álan Gomes (Acta Scientiae Veterinariae, 2017)
Background: Myxosarcomas (MXS) are malignant mesenchymal neoplasms originated from mainly mucin producing fibroblasts than collagen. Despite malignant neoplasms, MXS is believed to have low metastase generation ability. Myxosarcomas reports in dogs are widespread, usually involving trunk and limbs subcutaneous tissue. The aim of this report is to describe clinical, pathological, and immunohistochemistry aspects of a rare case of splenic myxosarcoma in a dog. Case: A 10-year-old, intact male Basset Hound, weiging 25 kg, showing signals such apathy, dark soft-stooled stools, progressive thinning, and increasing abdominal enlargement, perceived three months ago was brought to clinical consultation. Physical examination showed extremely pale oral and ocular mucosas, in addition to mild dehydration (6%), 35.4°C rectal temperature, and a very bulging abdomen, with no fluids or gases, evidence at abdominal percussion. A complete blood count (CBC) revealed neutrophilic leukocytosis and anemia. Patient´s abdominal cavity ultrasound examination showed an heterogeneous mass, occupying large part of cavity, and apparently from spleen origin. A spleenic multilobulated mass measuring 25 x 12 x 20 cm was obtained after exploratory laparotomy. The mass showed predominantly soft consistency with some firm areas, and no visible mesentery or other abdominal organs adhesions. Mass and spleen histopathological examination were routinely processed for histological analysis with haematoxylin and eosin and alcian blue staining. In addition, fragments of the neoplasm were submitted to immunohistochemistry (IHC) which confirmed myxosarcoma diagnosis. The owner returned to hospital two months after, complaining for apathy, prostration, anorexia, and abdominal pain. A new ultrasound examination were suggestive of liver and kidneys neoplasms. The tutor opted for patient´s euthanasia. However, dog´s necropsy was not authorized. Discussion: Myxosarcomas are malignant tumors considered rare in small animals, affecting mainly middle age or advanced age patients. Corroborating with the present case, the main clinical signs identified in cases of splenic neoplasias, in general, are abdominal distention and algia, emaciation, prostration, anemia, hypothermia, and inappetence. Regarding neutrophilic leukocytosis and anemia in CBC, those alterations are atributable to paraneoplastic syndromes commonly observed in small animals. The diagnosis of myxosarcoma was based on the pathological and IHC findings. The mesenchymal origin of the neoplastic cells was confirmed by the expression of vimentin and by the absence of cytokeratin labeling in the immunohistochemical examination. It was possible to confirm the diagnosis due to the presence of large amount of mucopolysaccharides between the neoplastic cells, demonstrated through Alcian Blue staining. Although rare, there have been reports of metastasis from cardiac myxosarcoma in humans and splenic myxosarcomas in dogs. The patient’s resubmission in two months with a new nonspecific clinical picture and documentation of hepatic and renal masses supports the possibility of agressive metastatic disease in the present case, despite the non-authorization of the autopsy examination. It was concluded by the present case report that MXS, although uncommon in small animals, should be included as a differential diagnosis in cases of abdominal neoplasias. The histopathological analysis and the immunohistochemical examination of neoplasms are important and should be considered in order to establish diagnosis and prognosis in dogs. Despite not confirmed by post-morten examination, agressive metastic disease seems likely in the present report, and emphasize MXS´malignat nature.